702To determine socio-demographic corelates of reproductive tract infection amongst women of reproductive age group. (2nd September 2021) - Gupta, Anmol
Abstract: Background: Reproductive tract infection (RTI) is a public health problem, in developing countries like India. The associated odium with it is a stumbling block in seeking health care. So, our aim was to studyprevalence of RTI symptoms and its socio-demographic corelates. Methods: A cross-sectional study was undertaken in the rural field practice area of Department of Community Medicine, Indira Gandhi Medical College, Shimla, Himachal Pradesh, India, from July 2018 to June 2019. Total sample size calculated was 410. Random sampling was used to select eligible couple to whom a predesigned, pretested, semi-structured and anonymousinterview schedule was administered after taking consent. Results: The prevalence of self-reported RTI'swas found to be 41.2%.It was more in lower socio-economic classes, and was statistically significant. Other socio-demographic corelates (age, education, occupation) did not showed any significant association. Conclusions: RTI infections were more prevalent among multigravida women and those using cloth during menstrual periods. RTIs are usually spurned by women and even the health care providers, so there is a need to give due consideration to this aspect of reproductive health. Key messages: The relevant and robust data on RTI's, may be secured by capacity building of health workers. An exemplary drug supply system may be ensured, so that the RTI kits are available at government health institutions. An introduction of affordable point-of-care tests for sexually transmitted infection may be done, as recommended in the WHO Global Health Sector Strategy for the control and prevention of STIs.